Two new species of Chusquea subg. Swallenochloa (Poaceae: Bambusoideae: Bambuseae) from Minas Gerais, Brazil, and complete description of C. caparaoensis - Machado Pianissola, Evandro; Freitas Parma, Daniele; Santos Gonçalves, Ana Paula; Gail Clark, Lynn (Phytotaxa, 2018)
Two new species included in Chusquea subg. Swallenochloa, C. fruticosa and C. imbricata, are here described and illustrated, and comments on their morphology, conservation status and distribution are provided. Reproductive structures of Chusquea caparaoensis, a species of this subgenus previously known only vegetatively, are described for the first time. Chusquea caparaoensis is here emended and illustrated, and comments about its morphology, conservation status and distribution are provided. Revised keys are provided based on vegetative and vegetative plus reproductive characters for the Brazilian species of C. subg. Swallenochloa.